2023
DOI: 10.1590/1413-812320232811.12692022
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de televisão, obesidade e doenças cardiovasculares em idosos brasileiros: Pesquisas Nacionais de Saúde 2013 e 2019

Elaine Cristina Lopes,
Letícia Martins Cândido,
Rafaela Aguiar Rosa
et al.

Abstract: Resumo Objetivou-se analisar a associação entre tempo assistindo televisão (TV) e a presença de obesidade isolada e associada às doenças cardiovasculares (DCV) de idosos brasileiros, conforme o sexo, comparando-se os dados das Pesquisas Nacionais de Saúde 2013 e 2019. Estudo transversal, com dados de 23.815 e 43.554 idosos das PNS 2013 e 2019, respectivamente. O autorrelato do tempo assistindo à TV foi categorizado em: <3, 3-6 e ≥6 horas diárias. A obesidade isolada foi avaliada pelo índice de massa corpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…These effects may be particularly pronounced among middle-aged and elderly individuals due to their declining physical fitness. A cross-sectional study conducted on older Brazilians revealed a positive association between extended screen times and heightened risk of obesity [ 19 ]. Ren et al’s investigation demonstrated that individuals aged 40 or above who exceeded two hours of daily screen time experienced a 30% increase in susceptibility to stroke [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be particularly pronounced among middle-aged and elderly individuals due to their declining physical fitness. A cross-sectional study conducted on older Brazilians revealed a positive association between extended screen times and heightened risk of obesity [ 19 ]. Ren et al’s investigation demonstrated that individuals aged 40 or above who exceeded two hours of daily screen time experienced a 30% increase in susceptibility to stroke [ 20 ].…”
Section: Discussionmentioning
confidence: 99%